The Spatial Context of Food Assistance: Examining Local Food Assistance Environment in the Context of SNAP. Issue 4 (4th July 2022) - Allard, Scott W.; Wathen, Maria V.; Danziger, Sandra K.
ABSTRACT: We develop the concept of the local food assistance environment to examine how spatial access to different local food assistance resources might shape food assistance program participation. Using unique survey data capturing Supplemental Nutrition Assistance Program (SNAP) participation in metropolitan Detroit, we explore how spatial access to local food assistance resources (e.g., SNAP offices, food retailers, charitable food assistance programs) may be associated with SNAP receipt. Descriptive analyses find that closer proximity to food assistance resources and retailers who accept food assistance benefits is positively associated with self-reported SNAP receipt.